2014
DOI: 10.1007/s10439-014-1095-4
|View full text |Cite
|
Sign up to set email alerts
|

Change of Direction in the Biomechanics of Atherosclerosis

Abstract: The non-uniform distribution of atherosclerosis within the arterial system has been attributed to pro-atherogenic influences of low, oscillatory haemodynamic wall shear stress (WSS) on endothelial cells (EC). This theory is challenged by the changes in lesion location that occur with age in human and rabbit aortas. Furthermore, a number of point-wise comparisons of lesion prevalence and WSS have failed to support it. Here we investigate the hypothesis that multidirectional flow—characterized as the average mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 35 publications
(67 reference statements)
1
86
0
2
Order By: Relevance
“…Flow splits to the arch branches were based on experimental measurements (Barakat et al, 1997) with 14.7% to the brachiocephalic trunk and 7.1% to the left subclavian artery, and 2% of the descending aortic flow to the ten intercostal arteries (see Mohamied et al, 2015). Murray׳s law (Murray, 1926) was used for further flow divisions to individual branches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow splits to the arch branches were based on experimental measurements (Barakat et al, 1997) with 14.7% to the brachiocephalic trunk and 7.1% to the left subclavian artery, and 2% of the descending aortic flow to the ten intercostal arteries (see Mohamied et al, 2015). Murray׳s law (Murray, 1926) was used for further flow divisions to individual branches.…”
Section: Methodsmentioning
confidence: 99%
“…The low, oscillatory WSS theory (Caro et al, 1971, Ku et al, 1985) underlies most current investigations of lesion localisation but not all studies have supported it (Peiffer et al, 2013b). Mohamied et al (2015) showed that the multidirectionality of WSS during the cardiac cycle, characterised by the transverse wall shear stress (transWSS) metric (Peiffer et al, 2013a), may be a more significant factor. Subsequent studies have shown that high transWSS is collocated with atherosclerotic plaque prevalence in minipigs (Pedrigi et al, 2015), and is associated with transitional flow instabilities in regions prone to wall remodeling (Bozzetto et al, 2015, Ene-Iordache et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Its direction and velocity during the cardiac cycle is complex, predictable, and includes directionality that is perpendicular to the mean bulk flow. 67 Furthermore, during systole disturbed flow is usually in the forward direction and reverses during diastole, with the location of the stagnation point (the site that momentarily has no flow) changing during the cardiac cycle. Turbulent flow has chaotic fluctuations, is irregular and unpredictable.…”
Section: Topographical Predisposition To Atherosclerosis and Intimal mentioning
confidence: 99%
“…Low shear stress can trigger intracellular cascades and shift phenotypic endothelial cell expression to an atherosclerotic prone state. Such endothelial cells display enhanced expression of inflammatory molecules and higher rates of apoptosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%